2010
DOI: 10.1007/s00415-010-5756-4
|View full text |Cite
|
Sign up to set email alerts
|

An early rise in body temperature is related to unfavorable outcome after stroke: data from the PAIS study

Abstract: Subfebrile temperature or fever is present in about a third of patients on the first day after stroke onset and is associated with poor outcome. However, the temporal profile of this association is not well established. We aimed to assess the relationship between body temperature on admission as well as the change in body temperature from admission to 24 h thereafter and functional outcome and death. We analyzed data of 1,332 patients admitted within 12 h of stroke onset. The relation between body temperature … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
40
2

Year Published

2012
2012
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 40 publications
(48 citation statements)
references
References 23 publications
6
40
2
Order By: Relevance
“…Other studies have indicated that it is not admissional body temperature that is associated with adverse outcomes of stroke, but the temperature peak occurring a few days after the stroke (18)(19)(20). The present study revealed that the more serious the stroke and the higher the NIHSS score, the more the body temperature increased.…”
Section: A B Csupporting
confidence: 49%
“…Other studies have indicated that it is not admissional body temperature that is associated with adverse outcomes of stroke, but the temperature peak occurring a few days after the stroke (18)(19)(20). The present study revealed that the more serious the stroke and the higher the NIHSS score, the more the body temperature increased.…”
Section: A B Csupporting
confidence: 49%
“…In both ischemic stroke and intracerebral hemorrhage, hyperthermia is a common complication that occurs in up to 30% to 40% of patients, and it is independently associated with poor outcome and increased mortality (32,70,71,77,125). Although intracerebral hemorrhage has been less studied than IS, and the underlying mechanisms may differ, the adverse outcome of hyperthermia (defined in this context as an average core temperature within the first 24 h of >37.5 • C) is similar with IS or intracerebral hemorrhage.…”
Section: Stroke and Heat Stressmentioning
confidence: 84%
“…Thus, recommendations highlight the importance of directly monitoring brain temperature (where possible and if needed) in patients with traumatic and ischemic injury, effectively managing fever and maintaining body temperature in a safe normothermic range (e.g., 36.7-37.0 • C [98.0-98.6 • F]) for at least the first several days after acute stroke or head injury (32,70,71,125).…”
Section: Stroke and Heat Stressmentioning
confidence: 99%
“…Recent clinical studies demonstrate that low body temperature within 6 hours of symptom onset is associated with severe ischemic stroke [2,20] and severe stroke subjects have relatively low body temperatures at admission within 12 hours of symptom onset in human subjects [21]. In animal models of experimental stroke, it is well known that controlledhypothermia is a neuroprotectant and a potential treatment in cerebral ischemia via reduction of energy requirements in the brain and protect the brain from infarct formation [22,23].…”
Section: Discussionmentioning
confidence: 99%